Simulation of optimal controls for thermal mode of sugar factory inclined diffusion apparatus - Lutska, Natalia; Kronikovskyy, Dmitry (My University, 2015)
The work compares two regulators for optimal temperature regime inclined diffusion apparatus of sugar factory. First synthesized by standard algorithms ACOr and second with same algorithm, but with the introduction of an integrated component on error signal. Based on the heat balance of the mathematical model of control object, which consists of eight linear differential equations, the model coefficients are calculated and presented it to the space of state variables. Based on the simulation show that the control system, which is synthesized by ACOr insignificant static error that allowed for technological regulations diffusion process. The use of optimal control algorithm with integral component of the error signal by significantly delaying transients in the system although it eliminates static error, because the latter algorithm impractical to use
Keywords: теплообмін; масообмін; дифузійний апарат; алгоритм; heat exchange; mass transfer; diffusion apparatus; algorithm; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка